Animal performance, economic analysis and digestibility in rabbits in the growth phase supplemented with silage - de Moraes Vieira, Maite; Porto Alegre Garcia, Renata; Bolico Soares, Dayxiele (Pubvet, 2021)
The use of fodder is a possibility in the reduction of the alimentary cost in the rabbit breeding due to the digestive physiology of this animal. The objectives of this work were to evaluate the animal performance, to analyze the economic viability and to evaluate the digestibility in rabbits supplemented with different types of silage. The experiment was conducted at IFRS, Ibirubá Campus. The rabbits were evaluated from 58 to 100 days of age. The experimental unit was one rabbit per cage. Four treatments and six repetitions were used. The treatments were basal diet (BD), basal diet plus oat silage supplementation (BD+OS), basal diet plus corn silage supplementation (BD+CS) and basal diet plus sorghum silage supplementation (BD+SS). The basal diet and silages were offered ad libitum throughout the trial period. The performance variable analyzed daily feed intake (DFI), daily silage intake (DSI), average daily gain (ADG) and feed conversion. In the economic analysis the total cost of feed and viability was calculated. The dry matter digestibility coefficient (DM), crude protein (CP), crude energy (CE), fiber in acid detergent (FAD), fiber in neutral detergent (FND) were analyzed. The DFI (g/day) was higher (P < 0.01) and the feed conversion better (P < 0.01) in animals that received the treatment with BD. The DSI was higher in the treatment with BD+CS (P < 0.01), 53 g/day. The lowest ADG was in the treatment with BD+OS (32 g/day). The economic viability was better using oat silage in supplementation. There was a difference (P < 0.05) in the dry matter digestibility coefficient (DMDC), being the treatment with BD and BD+SS with the highest coefficients (0.601 and 0.599, respectively). The supplementation with silage altered the digestibility of DM, CE, FND, FAD. The lower FAD digestibility coefficient was for BD (0.127) and the higher for BD+SS (0.737). The use of silage of oats, corn and sorghum in the feeding does not alter performance of rabbits in the phase of growth being viable the use in the feeding.